Riots and a blank canvas: young people creating texts, creating spaces - McIntyre, Joanna (Wiley, 2016)
This article draws on research into the work of Greenshoots,1 a small company of creative practitioners who provide opportunities for young people to work on projects involving visual and creative practices with a strong link to local heritage. Two specific projects form the focus of the paper: Riot and Blank Canvas. Both aimed to provide opportunities for young people to work with professional artists and performers to create a site-specific exhibition and performance in a disused warehouse space on the edge of the developing Creative Quarter in Nottingham. The projects took place out of school, and the research focused on the creative processes and practices involved in the production of texts created by the young people as they inhabited the space and developed, within a community of peers and artists, representations of that urban space. The article explores the ways in which the projects open up the potential for young people to engage with literacy practices, which traverse the boundaries of space, of art forms and of notions of culture and heritage. Two theoretical frames are used in the paper: Lave and Wenger’s “legitimate peripheral participation” (1991) and different scholars’ explorations of place-based approaches. In this way, the article aims to contribute to understandings of the diverse roles and potentials of young peoples’ creative practices and literacies in and out of school contexts.